2018
DOI: 10.1016/j.maturitas.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics, management and outcomes of older women with breast cancer in New Zealand

Abstract: The aim of this study was to understand the characteristics of older women with breast cancer and to describe the current patterns of treatment and outcomes. The study included data from the combined Auckland and Waikato breast cancer registers, which hold information for 12, 372 women diagnosed with stage I-IV breast cancer between June 2000 and May 2013. Of these women, 2671 (21.6%) were over 70 years of age. Patient characteristics, treatment type and survival were compared across four-year age groups (70-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…As noted above women who had diabetes were more likely to be older, be Māori, Pacific or Asian and have more comorbidities than women without diabetes. Previous studies have shown that older age and more comorbidities are significantly associated with decreasing use of surgery [3,[24][25][26]. Therefore, after adjustment for age, comorbidities and other factors, the gap in use of surgery for breast cancer between the diabetes group and the non-diabetes group narrowed, and the difference was only significant for women with stage I breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…As noted above women who had diabetes were more likely to be older, be Māori, Pacific or Asian and have more comorbidities than women without diabetes. Previous studies have shown that older age and more comorbidities are significantly associated with decreasing use of surgery [3,[24][25][26]. Therefore, after adjustment for age, comorbidities and other factors, the gap in use of surgery for breast cancer between the diabetes group and the non-diabetes group narrowed, and the difference was only significant for women with stage I breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Despite these findings, the role of postmastectomy radiation is not specific to subtype and often indicated for larger (T3) and node positive tumour, among other prognostic considerations. In the context of our results, the higher risk of locoregional and distant recurrence in early-onset patients may be driven by the fact that younger women are more likely to choose mastectomy [ 61 , 62 ] and may not be indicated for postmastectomy radiation for smaller, node negative disease. Cancello et al describe T1N0 disease as a spectrum from patients at very low risk for whom there is little evidence supporting the use of adjuvant therapy, to those with higher risk disease where an approach including chemotherapy plus targeted therapy appears clearly justified [ 63 ].…”
Section: Discussionmentioning
confidence: 96%
“…This study found that the costs of stage I-III breast cancer were associ- younger women were more likely to be diagnosed with advanced cancer and more aggressive subtype, and they receive more treatment than older women. 18,19 Increasing age was associated with decreasing use of surgery, adjuvant radiotherapy, endocrine therapy, and chemotherapy, even after adjustment for stage and level of comorbidity. 18,19 Before adjustment for other factors, M āori and Pacific patients seemed to incur higher public healthcare costs.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Increasing age was associated with decreasing use of surgery, adjuvant radiotherapy, endocrine therapy, and chemotherapy, even after adjustment for stage and level of comorbidity. 18,19 Before adjustment for other factors, M āori and Pacific patients seemed to incur higher public healthcare costs. However, after adjustment, M āori patients had equivalent costs, and Pacific patients had lower costs than others for both stage I-III cancer and stage IV cancer.…”
Section: Discussionmentioning
confidence: 99%